Gene susceptibility identification in a longitudinal study confirms new loci in the development of chronic obstructive pulmonary disease and influences lung function decline. Issue 1 (December 2015) - Xie, Jungang; Wu, Hongxu; Xu, Yuzhu; Wu, Xiaojie; Liu, Xue; Shang, Jin; Zhao, Jianping; Zhao, Junling; Wang, Jianmiao; Dela Cruz, Charles; Xiong, Weining; Xu, Yongjian
Abstract Background To identify COPD associated gene susceptibility and lung function in a longitudinal cohort including COPD and subjects who were at risk for developing COPD, and to replicate this in two cross-sectional and longitudinal populations in Chinese Han population. Methods Three cohorts were recruited in this study, including an 18-year follow-up population (306 COPD and 743 control subjects) in one village in 1992 and it changed to 409 COPD and 611 controls in 2010, a 2 year follow-up study in another village (374 COPD and 377 controls) and another 2 year follow-up one in a city (541 COPD and 560 controls) in 2010. Sixteen candidate single nucleotide polymorphisms (SNPs) were selected for genotyping. Among them, 5SNPs in or near HHIP, 1SNP in IREB2 and 1SNP in FAM13A were previously reported to be associated with COPD susceptibility or lung function decline. And another 9SNPs were selected from HapMap website as HHIP tags. In 2010, totaling 1, 324 COPD patients and 1, 548 healthy controls were finally included in our genetic susceptibility analyses. Results We identified two new regions showing an association with COPD susceptibility in the Human Hedgehog interacting protein (HHIP) rs11100865 and rs7654947, and we confirmed that the family with sequence similarity 13 member A gene (FAM13A) rs7671167 was associated with the development of COPD in Chinese Han population. And the HHIP rs7654947 and FAM13A rs7671167 were associated with lung function decline, and this result was replicated in other two populations. Conclusions These results suggest an important role of the HHIP and FAM13A regions as genetic risk factors for COPD development and lung function decline in Chinese Han population. Future research on these genes should focus on the molecular mechanisms of these genes on developing COPD and creating therapies to alleviate reduced lung function.